Osteoporosis knowledge, health beliefs, and healthy bone behaviours in patients on androgen‐deprivation therapy (ADT) for prostate cancer. (25th January 2013) - Nadler, Michelle; Alibhai, Shabbir; Catton, Pamela; Catton, Charles; To, Matthew J.; Jones, Jennifer M.
Abstract : What's known on the subject? and What does the study add?: There is an increase in use and duration of androgen‐deprivation therapy (ADT) in patients with prostate cancer. ADT can cause decreased bone mineral density and lean muscle loss, putting these patients at increased risk of fracture. Guidelines exist for the prevention and management of bone loss in this population; however, data suggests that most patients are not receiving proper screening, evaluation, or treatment for bone loss. Research to date suggests that patients on ADT are unaware of the risks and side‐effects of ADT and that most are not engaging in important preventative behaviours, e.g. calcium and vitamin D intake. To our knowledge, there are no studies in patients on ADT specifically assessing patients' osteoporosis (OP) knowledge, self‐efficacy, and feelings of susceptibility towards OP and their relationships to engagement in recommended healthy bone behaviours. We think that these data will aid in the development of health promotion uptake strategies that are directly targeted to this patient population. Objectives: To describe in patients with prostate cancer, receiving androgen‐deprivation therapy (ADT): (i) knowledge, self‐efficacy (SE), and health beliefs about osteoporosis (OP); (ii) current engagement in healthy bone behaviours (HBBs). To explore the relationships between knowledge, SE, and health beliefs, and engagement in HBBs. Patients and Methods: 175 patients receiving ADT by injection completed questionnaires assessing current HBBs, OP knowledge, SE, and health beliefs (motivation, perceived susceptibility, and seriousness). Descriptive statistics and independent samples t ‐tests were used to assess relationships between knowledge, SE, health beliefs, and engagement in HBBs. Results: Only 38% of patients had undergone a dual X‐ray absorptiometry scan in the past 2 years. OP knowledge was low (mean [sd, range] 9.6 [4.4, 0–19]) and perceived SE moderate (84.7 [24.5, 0–120]). Health motivation was fairly high (23.6 [3.1, 6–30]), but perceived susceptibility (16.8 [4.3]) and seriousness (16.8 [4.2]) of OP were low. Few patients met the recommendations for vitamin D intake (42%) and exercise (31%), and 15% were at risk of over‐supplementation of calcium. Patients taking calcium supplements ( P = 0.04), and meeting guidelines for vitamin D ( P = 0.008) and for exercise ( P = 0.002) had significantly greater knowledge than those who did not. Patients who were engaging in less than four of five HBBs had lower knowledge ( P < 0.001) and health motivation ( P = 0.01) than those who were engaging in four or all five HBBs. Conclusions: Most patients who are receiving ADT are not receiving appropriate screening, lack basic information about bone health, and are not engaging in the appropriate HBBs. These findings support the application of the Health Belief Model in this population: interventions that teach patients about the implications of bone loss, encourage proper uptake of HBBs, and promote feelings of SE could increase engagement in HBBs to prevent and manage bone loss.